The Level of Knowledge and Nurse Attitude in the Application of Five Moments Hand Hygiene in a Private Hospital in the Western part of Indonesia - Cornelia Ayu Kristina Larosa; Criesty Fransiska Junita Panjaitan; Belet Lydia Ingrit; Tirolyn Panjaitan (Nursing Current: Jurnal Keperawatan, 2022)
Hand hygiene is very important for health workers to reduce infection rates in health services area. Five Moments Hand Hygiene is one of strategy for health workers to keep safe from infections. Knowledge and attitudes by nurses about hand hygiene can influence nurse behavior and have an impact to improving patient health for reducing the spread of infection. To describe the level of knowledge and attitudes of nurses in applying the Five Moments Hand Hygiene in a Private Hospital in Wester part of Indonesia. This study used descriptive quantitative with the population are all nurses and the sample in this study were 46 nurses with total sampling technique. The instrument in the study used a questionnaire with level of knowledge and nurse attitude as variables. The data analysis technique is univariate. This study used ethical principles and has received ethical approval from The Research Committee Ethic Faculty of Nursing. The study shows  that nurses had a good (80,43%) knowledge of Five Moments Hand Hygiene but had a sufficient (54,35%) attitude in applying the Five Moments Hand Hygiene. Conclusion of this study is that most nurses have good knowledge but have sufficient attitude in applying Five Moments Hand Hygiene. For further researchers, it is recommended to find the relationship between knowledge and attitudes of nurses in applying the Five Moments Hand Hygiene.